Code‐expanded radio access protocol for machine‐to‐machine communications. Issue 4 (7th May 2013) - Thomsen, Henning; Pratas, Nuno K.; Stefanović, Čedomir; Popovski, Petar; Antón‐Haro, Carles; Lestable, Thierry; Lin, Yonghua; Nikaein, Navid; Watteyne, Thomas; Alonso‐Zarate, Jesus
ABSTRACT The random access methods used for support of machine‐to‐machine, also referred to as Machine‐Type Communications, in current cellular standards are derivatives of traditional framed slotted ALOHA and therefore do not support high user loads efficiently. We propose an approach that is motivated by the random access method employed in LTE, which significantly increases the amount of contention resources without increasing the system resources, such as contention subframes and preambles. This is accomplished by a logical, rather than physical, extension of the access method in which the available system resources are interpreted in a novel manner. Specifically, in the proposed scheme, users perform random access by transmitting orthogonal preambles in multiple random access subframes, in this way creating access codewords that are used for contention. We show that, for the same number of random access subframes and orthogonal preambles, the amount of available contention resources is drastically increased, enabling the massive support of Machine‐Type Communication users that is beyond the reach of current systems. Copyright © 2013 John Wiley & Sons, Ltd.